Necessidade de saúde: uma teorização fundamentada em vivências de profissionais de profissionais da Estratégia Saúde da Família - Elaine Miguel Delvivo Farão (2016)
This is a qualitative study conducted from the theoretical framework of the Symbolic and Methodological Interactionism of the Grounded Theory (GT). It was aimed to build theorizations about health needs based on professional experiences of the Family Health Strategy (FHS) and understand the conceptions of health needs of professionals working in Primary Health Care. Study participants are health professionals of the FHS in the city of Itabirito-MG, with five nurses, five community health workers, five nursing technicians and five physicians. Data were collected through interviews, which were recorded in electronic media and, subsequently, transcribed from the guiding questions: What do you mean by health needs? How does the service respond to the health needs? According to the methodological guidelines of GT, new questionings were added as the preliminary analyzes of data were taking place. Furthermore, notes on memos were written, which are notes made with basis on the interviews and that are filled with preliminary reflections about the impressions of the researcher and transformed into theoretical notes that help in the theorization held. Data were analyzed by means of the codification process proposed by the methodology, which has three stages: Open Data Codification, Axial Codification and Selective Codification. The key category that was raised, bringing together all the other properties and dimensions found in the concepts that contributed to its formulation, was: The (in) visibility of the health needs: the dynamicity of our coexistence with the world. This is because the theoretical constructs reveal that the health needs are comprised by those that are visible, which establish the causes of search for services on the part of users. Nevertheless, these are added to those that are invisible to professional care, and they severely affect not only the health-disease process of people, but also their lives. In order to achieve better effectiveness of care, they also need to be appreciated and transformed into needs possible to be addressed. It is hoped that this theorization may contribute to the implementation of more creative practices in the organization of health services, with a view to reaching a comprehensive care of the Health Needs, irrespective of whether they are visible or invisible.